Allelopathic tolerance of alfalfa (Medicago sativa L.) varieties to dodder (Cuscuta epithymum L.) - Marinov-Serafimov, Plamen; Golubinova, Irena; Marinova, Diana (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2017)
Allelopathic effects of cold water extracts of Cuscuta epithymum L. on seed germination and initial development of Medicago sativa L. varieties were investigated under laboratory conditions at the Institute of Forage Crops, Pleven, during 2016-2017. It was found that the water extracts from dry biomass of C. epithymum had a considerably stronger inhibitory effect on the studied M. sativa varieties (IR 32.7-100.0 %), as compared to the extracts of fresh biomass (IR 0.2-40.5%). Depending on the kind of C. epithymum extract (fresh or dry parasitic weed biomass), IRs for seed germination of the tested M. sativa varieties could be conventionally classified into five groups: 1) seed germination stimulation, -1.4% – extracts from fresh biomass affecting the variety „Multifoliolate“; 2) seed germination inhibition of 0.1-10% – extracts prepared from fresh biomass affecting the varieties „Prista 3“, „Pleven 6“, „Prista 5“ and „Obnova“; 3) seed germination inhibition of 11-20% – extracts from fresh biomass affecting the varieties „Roly“ and „Victoria“; 4) seed germination inhibition of 30-45% – extracts from dry biomass affecting the variety „Multifoliolate“; 5) seed germination inhibition of 46-60% – extracts from dry biomass affecting the varieties „Prista 5“, „Prista 3“, „Victoria“, „Roly“, „Dara“, „Pleven 6“ and „Obnova“.The varieties „Victoria“, „Prista 5“ and „Multifoliolate“ of M. sativa possess some allelopathic tolerance because their germination indexes (GI) range from 80.5 to 88.7 % for the extracts prepared from fresh weed biomass of C. epithymum, and from 47.1 to 48.6% for the extracts from dry weed biomass, compared to control treatment. These varieties can be used as components in future breeding programmes.
Keywords: Medicago sativa L.; Cuscuta epithymum L.; Allelopathy; Seed germination; Inhibition